Peluang dan Ancaman Disruptif Digital untuk Negara Berkembang - Junaedi, Dedi; Supriyatna, Rio Kartika; Arsyad, M. Rizal; Amalia, Rika Sri (Sci-tech Journal, 2023)
This research study aims to analyze digital disruptive opportunities and threats for the Indonesian state and nation. The method used in this research is qualitative analysis with a literature study approach. There are a number of digital economy practices that have caused Indonesia to lose potential state revenues. The interesting phenomenon of the case of Chinese tourists in Bali with WeChat Pay and Alipay has cost Indonesia foreign exchange, and is detrimental because the transactions are not recorded. The polemic about taxes on electronic transactions is still limited to tax collection in the e-commerce sector, while social media (Medsos) and over-the-top services (OTT) are still a polemic. This section also discusses mastery of data and transaction flows in the digital economy. The recommendations in this chapter focus on how Indonesia can address this “leakage”. One of them is through tax reform for e-commerce actors, equal level playing with businesses in Social Media, and other digital transactions. Keywords: opportunities and threats, digital disruptive